1996
DOI: 10.1108/14635789610153470
|View full text |Cite
|
Sign up to set email alerts
|

Obsolescence and performance in the Central London office market

Abstract: The economic theory of obsolescence A vintage model Ever since the pioneering article by Bowie (1982), the issue of depreciation has attracted growing attention in the UK commercial property market. This paper revisits the issue, from the perspective of what economic theory has to tell us about obsolescence, before embarking on an empirical case study of the Central London office market. The chosen theoretical approach is based on the "vintage model" of investment developed by Salter (1966) in his seminal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 3 publications
0
55
0
Order By: Relevance
“…Older buildings undergo more adaptation as time passes and it is not surprising to see age highly correlated with adaptation. Barras and Clark (1996) and Baum (1991) confirmed the correlation between time and obsolescence in buildings, demonstrating that as time passes some form of adaptation is essential to prevent a decline which otherwise can result in demolition.…”
Section: Component 3: Socialmentioning
confidence: 59%
See 2 more Smart Citations
“…Older buildings undergo more adaptation as time passes and it is not surprising to see age highly correlated with adaptation. Barras and Clark (1996) and Baum (1991) confirmed the correlation between time and obsolescence in buildings, demonstrating that as time passes some form of adaptation is essential to prevent a decline which otherwise can result in demolition.…”
Section: Component 3: Socialmentioning
confidence: 59%
“…Previous studies examining the criteria for building adaptation adopted a case study approach based on in-depth analysis of a relatively small sample of buildings (Austin, 1988;Barras and Clark, 1996;Ohemeng, 1996;Blakstad, 2001;Heath, 2001;Ball, 2002;Kincaid, 2002;Kucik, 2004;Arge, 2005;Remøy and van der Voordt, 2007). From these studies adaptation criteria were identified; however, the approach is 728 Wilkinson and Reed fundamentally different because of the detailed volume of data and the method used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hulten and Wykoff (1981a: 85) de® ne `economic depreciation' as a `decline in asset price due to ageing' . Previous property depreciation studies, with the exception of Barras andClark (1996, who built on Salter' s (1966) work), have tended to overlook this ® eld, which stems from the early work of Hotelling (1925), and is largely based on theoretical and empirical studies in the USA. Many of these studies have concentrated their efforts at a macro-scale level, and the debate has centred on the rate and pattern of depreciation to include in national income accounts and related tax allowances to re¯ect accurately the impact on real assets, such as plant and machinery and real estate.…”
Section: Critical Review Of Previous Depreciation Researchmentioning
confidence: 98%
“…Falling in¯ation during the early to mid-1980s had also concentrated fund managers' minds on the issue of depreciation, as it was no longer possible to mask the decline in relative property values due to depreciation (Baum, 1997). More recently, depreciation has continued during the 1990s (another period of low in¯ation and growth in the UK) to be a real issue, and one which is vital to consider in property valuation and investment appraisal (see, for example, Baum, 1991, 1997and Barras and Clark, 1996.…”
Section: Why Is Property Depreciation Important?mentioning
confidence: 99%